Creating Joyful Learning within a Democratic Classroom - Waterworth, Peter G. (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2020)
Learning is enhanced when it occurs within a positive environment where the learners feel a sense of passion and excitement about what they are learning. A joyful learning experience creates new neural pathways in the brain and enhances the acceptance of content. Learners learn more quickly and more deeply when their emotions are touched and the learning experience is accompanied by the positive feelings and reactions of their teacher and other fellow learners. This paper considers the factors and classroom processes that lead to positive learning sentiment and explores the way a teacher can create a suitable collaborative and democratic learning space.